Coping with Adolescence: Parents’ Experiences in Providing Sexuality Education to Deaf Adolescents - Stackus, Okwaput; Asnancie, Katumba (Universitas Pendidikan Indonesia (UPI), 2024)
Parents of Deaf adolescents are expected to provide sexuality education to their adolescents. This study explored how parents of Deaf adolescents acquire knowledge about sexuality education, the challenges they face in providing that education to their adolescents, and how they cope with the challenges. A qualitative approach was followed in the study. Methods of data collection were semi-structured interviews and focus group discussions. Data was collected from parents of Deaf adolescents. The findings indicate that parents obtain information about sex education from family members and formal education. However, their ability to provide that education is hindered by challenges such as a limited understanding of sexuality education, how to convey the information to Deaf adolescents, and inadequate skills in sign language. The authors recommend that parents of Deaf adolescents should be supported to acquire the knowledge and communication skills necessary for them to provide sex education to their adolescent children. In addition, the ministry responsible for education ought to put in place a policy that should guide the provision of sex education which is adapted for Deaf adolescents in schools.